A Study of Lexical Semantics in the Vocabulary of International Trade - Lydia U. EDET; Charles U. OGBULOGO; Innocent E. CHILUWA (Communications of International Proceedings, 2020)
Semantics theories have great relevance in human and business communication. As such, semantics as a subfield of linguistics emphasizes meaning in all spheres of life.  In this connection, semantics   has gone beyond the remit of the theoretical aspect of linguistics to the realm of providing practical solutions to human life. One of such areas of applicability of semantics is in the domain of international trade where meaning in business interactions can make or mar a business deal. This paper intends to identify the existence of lexical relations in the international trade vocabulary particularly in the Supply Chain Management (SCM) section.  A total of twenty terms selected from Supply Chain and Logistics glossary were analysed for their semantic information.   In line with the theory of lexical semantics which is concerned primarily with word meaning, definitions for the selected concepts were provided from the glossary. This engendered a link to their sense relations with other words in the supply chain vocabulary. Some of the sense relations which are also tools of analyses include antonymy, hyponymy and synonymy. In the Nigerian context, for example, there is paucity of studies on sense relations and meaning making mechanisms of online linguistic resources in international trade. It is this observation that provides motivation for this study. Thus, this study has implications for the clarity and understanding of SCM terms in international trade.
Keywords: Lexical Semantics; International Trade; Supply Chain Management